REPRESENTATION OF FEMINISM ON THE CHARACTER RAPUNZEL IN GRENO AND HOWARD’S FILM TANGLED - Syamsul Bahri; Nurjasni (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
From ancient times to the present, women have experienced a lot of discrimination. Discrimination against women is very dominant in the film Tangled. This statement attracts attention because women are often considered weak and not respected because women rely on laziness and are rarely free to act. Through the film Tangled by Greno and howard, which is based on the feminist theory of Tong and Botts (2009), this research aims to explore information about the variety of feminism that occurs in the film. This research uses a qualitative descriptive method which is usually as an approach to investigate the phenomenon of social problems. Data was taken from several images, dialogues and monologues from the film Tangled by Greno and howard and then analyzed contextually and theoretically. Researchers found that Radical Feminism was the most common, showing women being oppressed in any situation, liberal feminism also the common, In contrast psychoanalytic feminism is a minor feminism, social action related to a social system that places men as the main power holders and dominates in various roles.